1984
DOI: 10.1016/0014-5793(84)80904-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an inhibin preparation reveals apparent identity between a peptide with inhibin‐like activity and a sperm‐coating antigen

Abstract: The amino acid sequence of a large form of inhibin‐like peptide in human seminal plasma was determined, and compared with structures reported for similar inhibin preparations and a seminal plasma globulin. The data confirm and correlate previous reports on this form of inhibin‐like peptide. The structural comparisons further suggest that the peptide is closely similar to or possibly identical to a sperm‐coating antigen reported to be synthesized from prostatic epithelium. This may correlate with non‐gonadal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 12 publications
1
36
0
Order By: Relevance
“…The amino acid sequence of this peptide has been reported elsewhere (Sheth et al, 1984a;Johansson et al, 1984;Seidah et al, 1984). Antisera Rabbit antihuman seminal plasma ILM Specific rabbit antiserum raised by active immunization in this laboratory with the homogeneous preparation of ILM from seminal plasma, was used for immuno-staining of tissue ILM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The amino acid sequence of this peptide has been reported elsewhere (Sheth et al, 1984a;Johansson et al, 1984;Seidah et al, 1984). Antisera Rabbit antihuman seminal plasma ILM Specific rabbit antiserum raised by active immunization in this laboratory with the homogeneous preparation of ILM from seminal plasma, was used for immuno-staining of tissue ILM.…”
Section: Methodsmentioning
confidence: 99%
“…Of the various forms of inhibin-like materials (ILM) present in human seminal plasma, a peptide having a molecular weight of 10,400 daltons has been isolated in purified form from this laboratory (Thakur et al, 1981) the amino acid sequence of which has been reported (Sheth et al, 1984a; Johnson et al, 1984;Seidah et al, 1984). This peptide-ILM has been shown to be of prostatic origin (Sheth et al, 1984b;Beksac et al, 1984) and chemically similar (Johansson et al, 1984) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid (Johansson et al 1984, Seidah et al 1984, Akiyama et al 1985 and DNA sequences (Mbikay et al 1987, Green et al 1990) for PSP94 show no similarity with other known proteins. The PSP94 gene, however, has been shown to be similar in its upstream region to that of prostate-specific antigen (PSA) and prostatic acid phosphatase (PAP) , with respect to the presence of putative transcription regulatory elements for ubiquitous transcription factors, with the consensus sequences (Faisst & Meyer 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The protein has been detected in significantly reduced levels in other human tissues (Johansson et al 1984, Brar et al 1988, Lilja & Abrahamsson 1988, Ulvsback et al 1989, Weiber et al 1990, Teni et al 1992, Xuan et al 1995 and in mucous glands and various secretions (Weiber et al 1990).…”
Section: Introductionmentioning
confidence: 99%